Error Analysis Speaking on Foreign Speakers: Case Study of Brazilian Youtuber - Hesti Indah Mifta Nur’aini (Universitas Indraprasta PGRI, 2017)
Bahasa Indonesia both orally and in writing that have rules of order in order to be used effectively. Foreign speakers are part of the Indonesian language learners because Indonesian becomes a foreign language for the learner. In the learning process found various errors. The purpose of this research is to explain and describe Indonesian language by foreign speaker, youtuber from Brazil. This research uses descriptive qualitative method with approach. The data source used video from youtube. Technique of data completion using note note. Then, the data is compiled by mistake. The results of the study indicate the existence of language errors at the level of phonology and morphology.